2023
DOI: 10.1021/acs.orglett.3c00612
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Access to Tetrahydroxanthones via Copper-bis(oxazoline)-Catalyzed [4 + 2] Cycloaddition

Abstract: Highly enantioselective access to tetrahydroxanthone compounds was achieved through copper-bis(oxazoline)-catalyzed [4 + 2] cycloaddition of chrom-4-one dienophiles and Danishefsky’s diene. Oxo-dihydroxanthone (enone) adducts, containing a quaternary stereocenter, are generated in up to 98% yield and 89% ee. Cycloadducts are utilized in the synthesis of tetrahydroxanthones, featuring a novel organotin-mediated quasi-Krapcho decarboxylation of β-keto esters, with retention of stereochemistry. Tetrahydroxanthone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…[150] Attard et al in 2023 reported the synthesis of biologically relevant tetrahydroxanthone analogues 156 by copper-bis(oxazoline)-catalyzed [4 + 2] cycloaddition followed by an organotin-mediated quasi-Krapcho decarboxylation of β-keto esters (Scheme 42). [151] Initially, chrom-4-one dienophiles 153 and Danishefsky's diene 154 afforded oxo-dihydroxanthone (enone) adducts 155 containing a quaternary stereocenter in good yields and high enantiomeric excess. The cycloadduct 155 were utilized in the synthesis of 156 with retention of stereochemistry.…”
Section: Copper Catalyzed [4 + 2] Cycloadditionsmentioning
confidence: 99%
“…[150] Attard et al in 2023 reported the synthesis of biologically relevant tetrahydroxanthone analogues 156 by copper-bis(oxazoline)-catalyzed [4 + 2] cycloaddition followed by an organotin-mediated quasi-Krapcho decarboxylation of β-keto esters (Scheme 42). [151] Initially, chrom-4-one dienophiles 153 and Danishefsky's diene 154 afforded oxo-dihydroxanthone (enone) adducts 155 containing a quaternary stereocenter in good yields and high enantiomeric excess. The cycloadduct 155 were utilized in the synthesis of 156 with retention of stereochemistry.…”
Section: Copper Catalyzed [4 + 2] Cycloadditionsmentioning
confidence: 99%
“…Chromones are also useful building blocks for constructing diverse and complex heterocycles. 10–17 Among the chromone containing scaffolds, tricyclic chromone fused heterocycle compounds are quite important. Some of the tricyclic compounds are recurrent drugs or drug candidates, for example, the anti-inflammatory and anti-allergic drug amlexanox ( 1 ), 18 the anti-tubercular compound 2 , 19 the antimicrobial compound 3 , 20 and the antitumor compounds 4 (ref.…”
Section: Introductionmentioning
confidence: 99%
“…[5] For instance, the groups of Shibasaki [6] and Feng [7] reported independently efficient chiral Lewis acid-catalyzed enantioselective vinylogous additions using 2-ester-activated chromones as electrophilic donor, which is followed by Dieckmann cyclization to produce the tetrahydroxanthone-type natural products (Scheme 1a). In addition, the 3-EWG-activated chromones were also successfully applied in [4 + 2] annulation through chiral Lewis acid catalysis, [8] trienamine catalysis, [9] phosphine catalysis [10] to access various structurally diverse tetrahydroxanthones (Scheme 1b). Chi and co-workers reported the cascade reaction of chromone dienones with β-methyl enals promoted by N-heterocyclic carbene (NHC) to provide chiral hydroxanthone skeleton.…”
mentioning
confidence: 99%